2015
DOI: 10.1016/j.wem.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association of D Allele of ACE Gene With High Altitude Pulmonary Edema in Indian Population

Abstract: These findings demonstrate a possible association of the I/D polymorphism of the ACE gene with the development of HAPE, with D/D being the at-risk genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In the present study on 418 patients from western Black Sea region of Turkey, however, ACE gene I/D polymorphism and ACE gene alleles were not found to be associated with liver fibrosis severity. The ACE gene DD genotype is thought to be associated with an increased risk of rheumatic heart disease in the Saudi population (Al-Harbi et al, 2015), with nitric oxide metabolite levels and systolic blood pressure in clinically healthy Mexican men (no effect in women) (Avila-Vanzzini et al, 2015), with high altitude pulmonary edema in an Indian population (Bhagi et al, 2015), with sepsis susceptibility in Chinese patients (Yang and Zhou, 2015), with periodontal disease susceptibility in a Korean population (Kang et al, 2015), and with cancer risk in Caucasians (Zhang et al, 2014). It has been suggested that ACE gene I/D polymorphism is a genetic risk factor for Alzheimer's disease in a Chinese population (Yuan et al, 2015), while there is reportedly no association between ACE I/D gene polymorphism and a number of conditions and associated risks including type 1 diabetic nephropathy (T1DN) susceptibility and the risk of patients with type 1 diabetes mellitus developing T1DN in a Caucasian population , chronic obstructive pulmonary disease (Ayada et al, 2014) and retinal vein occlusion (Kutlutürk et al, 2014) in a Turkish population, as well as type 2 diabetic nephropathy (T2DN) susceptibility and the risk of patients with type 2 diabetes mellitus developing T2DN in Caucasian populations .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study on 418 patients from western Black Sea region of Turkey, however, ACE gene I/D polymorphism and ACE gene alleles were not found to be associated with liver fibrosis severity. The ACE gene DD genotype is thought to be associated with an increased risk of rheumatic heart disease in the Saudi population (Al-Harbi et al, 2015), with nitric oxide metabolite levels and systolic blood pressure in clinically healthy Mexican men (no effect in women) (Avila-Vanzzini et al, 2015), with high altitude pulmonary edema in an Indian population (Bhagi et al, 2015), with sepsis susceptibility in Chinese patients (Yang and Zhou, 2015), with periodontal disease susceptibility in a Korean population (Kang et al, 2015), and with cancer risk in Caucasians (Zhang et al, 2014). It has been suggested that ACE gene I/D polymorphism is a genetic risk factor for Alzheimer's disease in a Chinese population (Yuan et al, 2015), while there is reportedly no association between ACE I/D gene polymorphism and a number of conditions and associated risks including type 1 diabetic nephropathy (T1DN) susceptibility and the risk of patients with type 1 diabetes mellitus developing T1DN in a Caucasian population , chronic obstructive pulmonary disease (Ayada et al, 2014) and retinal vein occlusion (Kutlutürk et al, 2014) in a Turkish population, as well as type 2 diabetic nephropathy (T2DN) susceptibility and the risk of patients with type 2 diabetes mellitus developing T2DN in Caucasian populations .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of ACE in rats resulted in inflammation, pulmonary edema and histological changes in smoke inhalation-induced lung injury (31). In humans, the I/D polymorphism of the ACE gene has been associated with the development of high altitude pulmonary edema (32). The I/D ACE polymorphism has been demonstrated to be independent of thrombosis formation (33); however, it may be associated with osteoporosis (34), panic disorder (35) and vitiligo (36).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 304 cases and 564 controls were included in the pooled analysis. [10][11][12][13][14][15][16][17] The study characteristics are summarized in Table 1. Genotype distribution was consistent with HWE in the controls of all studies.…”
Section: Study Characteristicsmentioning
confidence: 99%